(untitled) (Journal of actual problems of jurisprudence, 2022)
This article discusses the specifics of the jurisdiction of individual labor disputes in the Republic of Kazakhstan. Today in Kazakhstan, the legal regulation of individual labor disputes is one of the key issues in the field of labor relations. At the present stage, there is a tendency to expand the judicial settlement of labor conflicts in the current legislation. However, it should be borne in mind that the judicial procedure for resolving individual labor disputes is expensive, lengthy and not too formal, and the court cannot equally satisfy the interests of both parties. All this negatively affects the relationship between the employee and the employer, which contributes to the growth of social tension. The occurrence of labor disputes usually precedes labor offenses in the field of Labor, which are the direct cause of the dispute. A labor offense is a non-performance or improper performance of labor duties in the field of labor, as well as separation, and therefore violation of the rights of another subject of this legal relationship. The methodological and theoretical basis of the work is the general scientific dialectical method of cognition, the empirical method, and the formal and logical method. Keywords: labor law, labor code, individual labor disputes, jurisdiction of individual labor disputes, court, conciliation Commission.